Lymphokine-mediated inhibition of Chlamydia replication in mouse fibroblasts is neutralized by anti-gamma interferon immunoglobulin. - Byrne, G I (1983)
Experiments were carried out to characterize immunologically mediated chlamydial persistence in cell culture. Mouse fibroblasts were activated to restrict Chlamydia psittaci 6BC replication by including mitogen (concanavalin A)-induced spleen cell supernatant fluids from immunized animals in the growth medium. When mouse fibroblasts were incubated with lymphokine for 24 h before infection and then with growth medium after infection (preinfection treatment), chlamydial replication was delayed but eventually detected. No substantial chlamydial growth occurred, even with extended incubation times when mouse fibroblasts were continuously exposed to lymphokine before and after infection. Low levels of infectious chlamydiae were produced in preinfection-treated mouse fibroblasts but not in mouse fibroblasts subjected to continuous lymphokine exposure. Incubation of lymphokine with anti-murine gamma interferon immunoglobulin neutralized the observed lymphokine-mediated activity, but incubation in the presence of anti-murine alpha plus beta interferon serum did not alter lymphokine activity. We conclude that the lymphokine components responsible for activating fibroblasts to restrict C. psittaci replication exhibits properties similar to gamma interferon.